DEFENDS: A Strategy for Creative Students - Fathoni, Mu`alim Ibu; Sumardi, Sumardi; Supriyadi, Slamet (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
DEFENDS is a strategy for defending position in writing. It is an acronym from Decide, Estimate, Figure, Express, Note, Drive and Search. In this strategy, students will follow the following steps: (1) decide on goals and theme, (2) estimate main ideas and details, (3) figure best order of main ideas and details, (4) express the theme in the first sentence, (5) note each main idea and supporting points, (6) drive home the message in the last sentence, and (7) search for errors and correct (Bisland, 2004: 57). For one thing, writing is one of four skills that are studied by students in learning English. Teacher needs to build the writing habit creatively. Whatever the reason, the teacher needs to help students build the writing habit so that they recognize writing as being a normal part of classroom practice and they come to writing tasks with as much enthusiasm as they do other activities (Harmer, 2007: 329). For another thing, creativity is the ability to produce original work and ideas (Kanematsu, 2016: 9). Tests of Creative Thinking (TCT) is used to find a creativity index and scores for various categories like fluency, originality, elaboration and flexibility. A quasi-experimental design is used in this study to prove the effectiveness of the strategy. The attributive variable of this study is studentsâ creativity. The test is in the form of writing test and creativity test.